Necesidad de regular en el art. 108 Código Civil y art. 123 del Código Orgánico de la Niñez y Adolescencia, el régimen de visitas a los hijos, por los cónyuges que se divorcian - Quinatoa Quinatoa, Luis Eduardo (2015)
When you run this research work pretend to give the lack of clarity of some legal provisions contained in our Ecuadorian law on visitation with the children by divorced parents. With which I think partly contribute to solving this social problem, allowing the system to be administered to expand the days and times of visits mainly to the parent who lives with the child, in order to maintain or increase the love and affection between parents and children, and thus ensure the comprehensive development, understood as the process of growth, maturation and deployment of their intellect and their capabilities, potential and aspirations, in a family, school, social and community affection and security, because by not regulated in the divorce decree only allows the parent to visit the minor children on weekends either two or three hours daily. I can state with certainty that this work is likely to run, since I have extensive information of the literature and is also a socio-legal problem that affects children under the age of families broken by divorce. It is evident that at present due to various social, economic and moral within the family at the local, national and world we live in, have affected there is a high divorce rate and thus the destruction of homes. Many parents can not visit their children on the ground that the judgments handed down by judges or judges in divorce proceedings and the tenure do not have clear regulations for visits from parents to children, divorce decree are not well regulated parental visits to children, why is issued only two hours a day or just weekends, causing serious family conflicts between the estranged couple have a direct impact negatively on the minor children as resentment, depression, low self-esteem, poor school performance, suicide, etc.., so attentive to the provisions of Art 44 of the Constitution of the Republic of Ecuador, which says the state, society and promote the family so priority integral development of children and adolescents, and ensure the full exercise of their rights will be addressed early in their best interests and their rights will prevail over those of others. The children and adolescents have the right to integral development, understood as a process of growth, maturation and deployment of their intellect and their capabilities, potential and aspirations, in a family, school, social and community of affection and security. This environment will allow the satisfaction of their social, affective-emotional and cultural, with the support of local and national intersectoral policies